Falsafah dan Strategi Politik Dakwah PKS - WARJIO WARJIO (Universitas Sumatera Utara, 2011)
The Party system in Indonesia known Partai Keadilan Sejahtera (PKS) as the Partai Dakwah. This fact gives a difference with the other parties in Indonesia. This study discusses how the ac-tual philosophy and grand strategy of Partai Keadilan Sejahtera (PKS) as the Partai Dakwah. The study found that the basic philosophy of PKS is based on the principle for improv-ing people, or it can be regarded as a universal missionary movement (dakwah syamilah) as a process of self purification and as God's servant. Political strategy dakwah PKS through- cultural movement (horizontal mobility strategy/ta’biah al afaqiyah) and structural movement (vertical mobility strategy/ta’biah al amudiyah). All of that becomes an important feature of the PKS as a Partai Dakwah and stressed how The PKS true face as a Partai Dakwah. PKS aware-that political parties can not perform its function without broad community support.Keywords: Islamic party, political strategy, political philosophy.